Interplay of Heat Shock Proteins and Oxidative Stress in Modulating Neutrophil Activation in Cystic Fibrosis Inflammation - Arif Malik; Jehanzaib Islam; Anoosh Qayyum; Haleema Saadia; Gul Zaib; Ayesha Zahid (Pakistan Journal of Medicine and Dentistry)
Background: Cystic fibrosis, is an autosomal recessive disorder characterized by persistent inflammation, unregulated immune responses, and pneumonic complications. The central role of CF-associated inflammation is neutrophil activation triggered by oxidative stress and Heat Shock Proteins (HSPs). The present study seeks to explore the interaction of oxidative stress, HSPs, and neutrophil activation in CF patients.